A COMPARATIVE STUDY ON MALE AND FEMALE STUDENTS’ COMPREHENSION OF NON-GENDER BIAS TEXTS - Johanis Anton Emilo Reyaan; Sarah Kamagi; Aloysius Rettob (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The present study deals with male and female students’ reading comprehension. The purpose is to describe the effect of gender on reading comprehension of neutral or non-gender biased texts. The study is experimental in nature and conducted online through WA and email. The study involved two classes of eight grade students of SMP Negeri Tompaso in academic year 2020-2021.  The data are collected using a reading test in multiple-choice format. The data collected are statistically analyzed. Result of the analysis leads to the conclusion that there is no difference between female and male students’ reading comprehension performance on gender free bias texts. Put it another way, gender does not affect reading comprehension performance. This conclusion supports William (2000) who affirms that sex differences in cognition are small or have no effect on comprehension. However, since it is conducted online, control over extraneous variables could not be strictly carried out; therefore, more studies are needed to obtain more information about effect of gender on comprehension.